2007
DOI: 10.1111/j.1756-2171.2007.tb00043.x
|View full text |Cite
|
Sign up to set email alerts
|

Does Sutton apply to supermarkets?

Abstract: This paper presents empirical evidence that endogenous fixed costs play a central role in determining the equilibrium structure of the supermarket industry. Using the framework developed in Sutton (1991), I construct a model of supermarket competition where escalating investment in firm level distribution systems is driven by the incentive to produce a greater variety of products in every store. Using the observed networks of store and warehouse locations, I identify 51 distinct geographic markets covering nea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
125
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 171 publications
(140 citation statements)
references
References 10 publications
14
125
0
1
Order By: Relevance
“…club cards), its importance has declined in recent years. 1 0 The speci…c details of how these markets were constructed are described in Ellickson (2007), which also establishes the relatively high degree of independence between these markets by matching each store to its primary distribution center and measuring the degree of spillover across markets. In particular, I …nd that stores supplied by an out of market distribution facility owned by the parent …rm account for, on average, less than 10% of total sales.…”
Section: Quality Competition In the Supermarket Industrymentioning
confidence: 99%
See 3 more Smart Citations
“…club cards), its importance has declined in recent years. 1 0 The speci…c details of how these markets were constructed are described in Ellickson (2007), which also establishes the relatively high degree of independence between these markets by matching each store to its primary distribution center and measuring the degree of spillover across markets. In particular, I …nd that stores supplied by an out of market distribution facility owned by the parent …rm account for, on average, less than 10% of total sales.…”
Section: Quality Competition In the Supermarket Industrymentioning
confidence: 99%
“…To do so, I rely on prior empirical results presented in two previous papers. In Ellickson (2007), I empirically established the relevance of natural oligopoly at the market level. In particular, I demonstrated that, across the full set of distribution markets, between 4 and 6 …rms capture 60 to 70% of sales.…”
Section: Quality Competition In the Supermarket Industrymentioning
confidence: 99%
See 2 more Smart Citations
“…11281986. The geographic areas encompassed by a Scantrack are also roughly consistent with the supermarket distribution regions designated in Ellickson (2007). in the "processed canned/bottled foods" group, and dinner sausages are contained in the "refrigerated meats" group.…”
Section: Total Sales Cmtmentioning
confidence: 57%